LncRNA-241 inhibits 1, 2-Dichloroethane-induced hepatic apoptosis. (December 2019) - Zeng, Ni; Zhang, Zhen; Jiang, Hongmei; Li, Ruobi; Chang, Chong; Wang, Fei; Xu, Dandan; Fan, Qiming; Wang, Ting; Xiao, Yongmei; Chen, Wen; Shan, Zhixin; et al.
Abstract: Chlorinated organic chemical 1, 2-dichloroethane (1, 2-DCE) is used widely in industrial production processes, and excessive exposure may lead to liver damage. The mechanisms underlying 1, 2-DCE-induced hepatotoxicity are not fully understood. Numerous studies have demonstrated that long-non-coding RNAs (lncRNAs) play a pivotal role in the chemical-induced toxicity. To explore whether aberrant lncRNA expression is involved in hepatotoxicity mediated by 1, 2-DCE exposure, we detected alterations of lncRNA expression profiling in a mouse model of 1, 2-DCE-induced hepatotoxicity by microarray chip. Bioinformatic analysis indicated that a down-regulated lncRNA (lncRNA241) after 1, 2-DCE exposure might be involved in 1, 2-DCE-induced hepatotoxicity. We treated AML12 cells with 1, 2-DCE and its metabolite 2-chloroacetic acid (2-CA) for 48 h, and the results revealed that it was 2-CA rather than primary form (1, 2-DCE) that resulted in the decline of lncRNA241 expression in hepatocytes. In vitro intervention studies revealed that the repression of lncRNA241 expression after 2-CA exposure led to the down-regulation of anti-apoptosis-associated factor insulin growth factor-1 ( Igf1 ) at mRNA and protein levels through modulation of their common target mmu-miR-451a, which promoted hepatic apoptosis. This study provides valuable insight into the role of lncRNAs in response to hepatocyte apoptosis induced by 1, 2-DCE. Graphical abstract: Unlabelled Image Highlights: Exposure of 1, 2-DCE can result in the downregulation of LncRNA241 expression in the liver tissue of mice. The decline of lncRNA241 expression in hepatocytes might be mediated by 1, 2-DCE's metabolite 2-chloroacetic acid (2-CA). LncRNA241 can regulate the expression of mmu-miR-451a and Igf1 and involve in the hepatocyte apoptosis.